Uterine Artery Pseudoaneurysm in the Setting of Delayed Postpartum Hemorrhage: Successful Treatment with Emergency Arterial Embolization - Ankur M. Sharma; Brent E. Burbridge (Case Reports in Radiology)
Postpartum hemorrhage is a major cause of maternal mortality. Though uncommon, uterine artery pseudoaneurysm can follow uterine dilatation and curettage (D + C) and needs to be considered in the differential diagnosis. This 30-year-old G1P1 woman presented with right upper quadrant pain and vaginal bleeding. She was afebrile but her white blood count was significantly increased (22.2×109 /L). One week prior, she had undergone a Cesarean delivery which was complicated by hemolysis, elevated liver enzymes, and low platelet count syndrome (HELLP), fetal dystocia, and chorioamnionitis. Uterine dilatation and curettage (D & C) and placement of a Bakri intrauterine balloon, performed for suspected retained products of conception, failed to control her postpartum bleeding. The patient wished to have a hysterectomy only as a last resort in order to preserve fertility. Emergency uterine artery angiography revealed a left uterine artery pseudoaneurysm and contrast extravasation. The patient was successfully treated with selective embolization. Computed tomography (CT) later revealed dehiscence of her uterine Cesarean section incision with an intra-abdominal fluid collection. This collection was drained. She also developed disseminated intravascular coagulopathy (DIC) syndrome as well as multiple pulmonary emboli which were both successfully treated. We discuss this unique case of uterine artery pseudoaneurysm with associated uterine dehiscence.